Extrachromosomal circular DNA in cancer drug resistance and its potential clinical implications - Luo, Juanjuan; Li, Ying; Zhang, Tangxuan; Xv, Tianhan; Chen, Chao; Li, Mengting; Qiu, Qixiang; Song, Yusheng; Wan, Shaogui (Frontiers in Oncology, 2023)
Chemotherapy is widely used to treat patients with cancer. However, resistance to chemotherapeutic drugs remains a major clinical concern. The mechanisms of cancer drug resistance are extremely complex and involve such factors such as genomic instability, DNA repair, and chromothripsis. A recently emerging area of interest is extrachromosomal circular DNA (eccDNA), which forms owing to genomic instability and chromothripsis. eccDNA exists widely in physiologically healthy individuals but also arises during tumorigenesis and/or treatment as a drug resistance mechanism. In this review, we summarize the recent progress in research regarding the role of eccDNA in the development of cancer drug resistance as well as the mechanisms thereof. Furthermore, we discuss the clinical applications of eccDNA and propose some novel strategies for characterizing drug-resistant biomarkers and developing potential targeted cancer therapies.